The kingdom by the sea - Westall, Robert (London : HarperCollins Children's Books, 2009)
During World War II twelve-year-old Harry and a stray dog travel through war-torn England in search of safety.
6.3
5-8.
5-8
Keywords: Dogs -- Fiction; World War, 1939-1945 -- England -- Fiction; Dogs -- Fiction; World War, 1939-1945 -- England -- Fiction; England -- Fiction; England -- Fiction